Exploring the social and emotional context of childhood animal cruelty and its potential link to adult human violence - Hensley, Christopher (Psychology, crime & law, 2018)
Those who commit acts of animal cruelty may do so differently based upon how they individually experience such acts. These experiences may impact the link that exists between childhood animal abuse and later interpersonal violence. Limited research exists that examines how social and emotional factors such as being upset after committing animal cruelty may impact the progression from early acts of animal cruelty to later acts of adult violence against humans. Based on responses from 180 prison inmates in a Southern state, the current study examined the effects of onset and frequency of animal cruelty, covertness of animal cruelty, the commission of animal cruelty alone or in a group, and being upset after committing animal cruelty. Inmates who committed recurrent acts of childhood animal cruelty were more likely to commit recurrent acts of adult interpersonal violence.